The Relationship Between Bone Mineral Density and Periodontitis in Postmenopausal Women - Tezal, Mine; Wactawski‐Wende, Jean; Grossi, Sara G.; Ho, Alex W.; Dunford, Robert; Genco, Robert J. (Journal of periodontology (1970), 2000)
Background: Systemic bone loss has been proposed as a risk factor for periodontal disease; however, the relationship between these two diseases is still not clear. The objective of this study was to assess the relationship between systemic bone mineral density and periodontal disease, controlling for known confounders. Methods: The study population included 70 postmenopausal Caucasian women aged 51 to 78 (mean ± SD: 62.10 ± 7.1 years). Skeletal bone mineral density (BMD) was assessed by dual energy x‐ray absorptiometry (DXA) at the neck, trochanter, intertrochanter, Ward's triangle, and total regions of the femur, and from the anterior‐posterior view of the lumbar spine. Periodontal disease severity was represented by clinical attachment loss (CAL) and interproximal alveolar bone loss (ABL). Other measures of periodontal status included probing depth (PD), supragingival plaque, gingival bleeding on probing, and calculus. DXA and oral examinations were performed by calibrated examiners. Partial correlation coefficients (r) were obtained from multiple linear regression analysis adjusting for age, age at menopause, estrogen supplementation, cigarette smoking, body mass index, and supragingival plaque. Results: Mean ABL was significantly correlated with BMD of the trochanter (r = − 0.27), Ward's triangle (r = −0.26), and total regions of the femur (r = −0.25). Mean CAL appeared to be related to BMD consistently at all regions of the skeleton, although the association did not reach statistical significance. Conclusions: We can conclude that skeletal BMD is related to interproximal alveolar bone loss and, to a lesser extent, to clinical attachment loss, implicating postmenopausal osteopenia as a risk indicator for periodontal disease in postmenopausal Caucasian women. J Periodontol 2000;71:1492‐1498.